Peran Komisaris Indepeden Memoderasi Hubungan Ukuran Perusahaan, Profitabilitas dan Financial Leverage terhadap Income Smoothing - Eny Maryanti; Sarwenda Biduri; Herlinda Maya Kumala Sari (Owner : Riset dan Jurnal Akuntansi, 2023)
Income smoothing is a general phenomenon that is quotated for variability to reduce the income reported to reduce market risks for regulatory shares. The income of this smoothing action has been considered a logical and rational action, but can harm other parties. This research is a queue to meet the role of independent commissioners in moderating the relationship of company size, profitability and financial leverage to the practice of profit in manufacturing companies that are registered with the Stock Exchange Exchange. The population of manufacturing companies registered in the Indonesia Stock Exchange in 2016-2021, Number of Research Samples 330. This research is the logistics regression examination method, SPSS Software. Income income is measured using the Eckel index. The independent variables in this study are the size of the company (LN Total sales), profitability (ROE), liquidity (debt of total assets), and independent commissioners as moderation variables. The results showed that the measurement of the careless had a significant negative effect while leverage had a significant positive effect but profitability had no effect on income income. Commissioners strengthen strengthening the relationship of company size tangkapan income smoothing and commissioners weaken the independent relationship of leverage income income income income. However, independent commissioners cannot moderate the profession of professional income. Large regulations will be more careful and have the courage to unkul in the risk of making reports that tend not to practice income income. Gurrivals who have a high profit that Tenji practices income to improve and decrease in profit, because the company is careful in boiling profit and gain of Kanca Pini Lapananaan to make a debt of one of the bahang ways to do with the practice of revenue removal. The Board of Commissioners has an independent mushroom in supervising and controlling the principal applied by the school to avoid irregularities.